Cross-sectional earnings risk and occupational sorting: the role of risk attitudes - Holger Bonin; Thomas Dohmen; Armin Falk; David Huffman; Uwe Sunde (Institute for the Study of Labor (IZA), 2006)
This paper investigates whether risk preferences explain how individuals are sorted into occupations with different earnings variability. We exploit data from the German Socio-Economic Panel, which contains a subjective assessment of willingness to take risks whose behavioral relevance has been validated in previous work. As a measure of earnings risk, we use the cross-sectional variation in earnings that is left unexplained by human capital in Mincerian wage regressions. By relating earnings risk to the measure of individual risk preference, our evidence shows that individuals with low willingness to take risks are more likely to be sorted into occupations with low earnings risk. This pattern is found regardless of the level of occupation categories, region, gender and labor market experience. We also find that risk preferences are significant determinant of wages in a Mincer regression, illustrating the importance of preferences and attitudes in addition to more standard regressors.
Keywords: J24; J31; D01; D81; 330; occupational choice; sorting; risk preferences; GSOEP; earnings risk; Berufswahl; Risikopräferenz; Bildungsertrag; Einkommen; Risiko; Theorie; Deutschland